Organic fouling in RO processes - Ang, John Wee Heng (2018)
Freshwater is a very important resource for humanity and it is getting increasingly scarce. As a result it is important to find alternative sources or technologies to supplement the scarcity of clean portable drinking water. With that in mind, reverse osmosis membrane technology is a great option for seawater desalination and it is more commonly adopted due to its benefits as compared to other desalination technologies. However, there are problems associated with the operation of seawater desalination utilising reverse osmosis membranes. Membrane fouling has been a nagging issue affecting the productivity of clean water by RO membrane seawater desalination. With the presence of organic matter in raw seawater, it is the main foulant leading to RO membrane fouling. Therefore the purpose of this study is to understand the fouling interactions between each organic foulant and membrane surface to determine their propensity to cause organic fouling. To study the effects of fouling, the XDLVO theory was utilised in this project to predict the interactive adhesion energies. The results of the XDLVO theory revealed that with the addition of divalent cations to the feed solution, the attachment between two surfaces will become stronger as compared to a feed solution with only monovalent cations. However this does not lead to more significant membrane fouling and flux drop in every fouling experiment. With the information obtained from this study, solutions to mitigate such membrane fouling in seawater desalination applications can be developed to better increase the productivity and efficiency of the SWRO process and then supplementing the freshwater scarcity situation.